2020
DOI: 10.1080/17430437.2020.1844183
|View full text |Cite
|
Sign up to set email alerts
|

Examining attitudes towards homosexuality among young, athletic BME men in the UK

Abstract: This article examines the influence of ethnicity on sporting men's attitudes towards homosexuality. We employed Herek's Attitudes Toward Lesbians and Gay Men, Revised Version (ATLG-R) scale to collect data with British undergraduate sports students, as well as interview data with the players of an English Premier League (EPL) football academy, to show that black and minority ethnic (BME) men espouse more conservative attitudes toward homosexuality than their White counterparts. This, we theorize, is attributab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…The scale has been validated with English-speaking samples [16,[27][28][29] and translated versions of the scale have been tested for validity with a number of non-English-speaking samples, including Asian populations [24,30,31] and even Asian samples with social work backgrounds [32]. The scale is in current use in a wide range of fields including sexuality research [33], environmental research and public health [34], psychology [35], homosexuality studies [36], pedagogy [37], psychiatric care in nursing [38], and sports [39]. The ATLG consists of 20 different statements, 10 about gay men (Attitude Toward Gay Men-ATG subscale) and 10 about lesbian women (Attitude Toward Lesbians-ATL subscale) to which respondents indicate their levels of agreement or disagreement (Herek, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…The scale has been validated with English-speaking samples [16,[27][28][29] and translated versions of the scale have been tested for validity with a number of non-English-speaking samples, including Asian populations [24,30,31] and even Asian samples with social work backgrounds [32]. The scale is in current use in a wide range of fields including sexuality research [33], environmental research and public health [34], psychology [35], homosexuality studies [36], pedagogy [37], psychiatric care in nursing [38], and sports [39]. The ATLG consists of 20 different statements, 10 about gay men (Attitude Toward Gay Men-ATG subscale) and 10 about lesbian women (Attitude Toward Lesbians-ATL subscale) to which respondents indicate their levels of agreement or disagreement (Herek, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Outside of sport, recent research with working-class boys and men (e.g., Blanchard, McCormack & Peterson, 2015;Roberts, 2018) also documents positive attitudes toward homosexuality, as well softer and more inclusive forms of masculinity compared to older research (e.g., Nayak & Kehily, 1996). While research with non-white men in Anglo-American contexts has shown improved attitudes (e.g., Morales, 2018), other research still documents generally more conservative attitudes among these groups of men (Magrath, 2017b;Magrath, Batten, Anderson & White, 2020;Southall, Anderson, Nagel, Polite & Southall, 2011).…”
Section: Debatesmentioning
confidence: 97%
“…Anti-homosexual attitudes persist notably in religious communities, it was also stated that research into other cultural experiences at the time were significantly lacking. That statement has changed in recent years and led to the uncovering of data relating to Black & Minority ethnic groups, according to the work of Magrath et al (2020), these groups are identified in the UK as holding the most conservative views, regarding sexuality, in comparison to their white British peers. Influence from church congregations appears to be a consistency in the development of these attitudes, as highlighted by Magath et al (in reference to US BME) 'The church in the UK also remains central to many BME communities as a centre for protecting traditional culture and a physical or psychological place for performing identity'.…”
Section: Homophobiamentioning
confidence: 99%